2008
DOI: 10.1177/1933719108323446
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of Medroxyprogesterone Acetate, an Androgenic Ligand, in Ovarian Cancer Cell Invasion

Abstract: Although classified as a progestin, medroxyprogesterone acetate has significant androgenic activity unique from the pure androgen dihydrotestosterone. Our studies suggest that pharmacologic doses of medroxyprogesterone acetate may actually increase the invasive potential of epithelial ovarian cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It was additionally shown that DHT induced cell motility and invasion of an ovarian cancer line [79]. Methyltrienolone [76] and another AR ligand, medroxyprogesterone [80], also increased the ability of cell invasion of AR-positive ovarian cancer lines, although the latter is classified as a progestin. All of these studies have thus demonstrated in vitro and in vivo data indicating that androgens promote cell proliferation/invasion of ovarian cancer via the AR pathway.…”
Section: Role Of Androgens and Ar Signaling In Ovarian Cancer Progmentioning
confidence: 99%
See 1 more Smart Citation
“…It was additionally shown that DHT induced cell motility and invasion of an ovarian cancer line [79]. Methyltrienolone [76] and another AR ligand, medroxyprogesterone [80], also increased the ability of cell invasion of AR-positive ovarian cancer lines, although the latter is classified as a progestin. All of these studies have thus demonstrated in vitro and in vivo data indicating that androgens promote cell proliferation/invasion of ovarian cancer via the AR pathway.…”
Section: Role Of Androgens and Ar Signaling In Ovarian Cancer Progmentioning
confidence: 99%
“…All of these studies have thus demonstrated in vitro and in vivo data indicating that androgens promote cell proliferation/invasion of ovarian cancer via the AR pathway. Nonetheless, conflicting findings have been documented in two studies that show significant inhibition of the cell viability of 25 primary cultures established from various subtypes of ovarian carcinomas as well as borderline and benign tumors by 0.1 pM–100 nM testosterone [81] and marginal inhibition of ovarian cancer cell invasion by 1 µM DHT [80].…”
Section: Role Of Androgens and Ar Signaling In Ovarian Cancer Progmentioning
confidence: 99%
“…The ovarian cancer cells express AR and respond to androgen with increased proliferation and attenuated apoptosis. Over-expression of AR has been found in ovarian cancer, and once activated, it can stimulate ovarian cancer cell invasion (Gogoi et al, 2008;Ligr et al, 2011), indicating targeting AR is also a promising treatment strategy.…”
Section: Mapk and Ovarian Cancermentioning
confidence: 99%
“…DHT acts as an agonist for AR, thereby inducing the proliferation and invasiveness of various OVC cells ( 78 , 81 ). However, an intriguing study by Gogoi and colleagues showed that DHT and medroxyprogesterone acetate, an androgenic ligand, act by upregulating the inflammatory cytokines, IL-6 and IL-8 and downregulating the matrix metalloproteinases, MMP-2 and MMP-9 in OVC cells ( 79 ). Similarly, in another study, DHT increased cell proliferation in SKOV3 cells by elevating the IL-6 and IL-8 levels, which was reversed by treatment with an AR antagonist, flutamide ( 78 ).…”
Section: Nrs In Ovcmentioning
confidence: 99%